2021
DOI: 10.1016/j.adro.2021.100727
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging for Breast Tumor Bed Delineation: Computed Tomography Comparison and Sequence Variation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(96 reference statements)
0
6
0
1
Order By: Relevance
“…Fiducials were used to aid in seroma boundary delineation 23 in 18 of 21 treatment sites as it has been previously shown that they reduce interobserver variability for target delineation. 24 Sufficient contrast between seromas and healthy tissue was present for the remaining 3 targets, thus fiducials were omitted. In the reference CT structure set, fiducials were assigned to titanium alloy and nearby artifact created by fiducials was assigned to water.…”
Section: Methodsmentioning
confidence: 99%
“…Fiducials were used to aid in seroma boundary delineation 23 in 18 of 21 treatment sites as it has been previously shown that they reduce interobserver variability for target delineation. 24 Sufficient contrast between seromas and healthy tissue was present for the remaining 3 targets, thus fiducials were omitted. In the reference CT structure set, fiducials were assigned to titanium alloy and nearby artifact created by fiducials was assigned to water.…”
Section: Methodsmentioning
confidence: 99%
“…Se obtiene una mejoría significativa del índice de conformidad interobservador al utilizar una resonancia magnética con secuencia T1-supresión grasa en comparación con la tomografía de simulación [22][23][24][25]. El "Canadian Cancer Research Journal Oncology 2020", realizó un consenso sobre la localización del lecho tumoral, incluyendo 20 expertos, quienes recomiendan lo siguiente: deben colocarse clips quirúrgicos a lo largo de las 4 paredes laterales de la cavidad, más 1-4 clips en el margen posterior si es necesario (evitar su uso fuera del lecho); la realización de informes quirúrgicos para orientar de forma precisa a los oncólogos radioterapeutas en cuanto; al tamaño, localización del tumor, el tamaño del defecto y datos específicos del procedimiento (tipo, rotación de tejido, coordenadas de los clips) [22].…”
Section: Resultsunclassified
“…Our study is significant as it details protocols and processes developed in-house to deliver radiation planning scans at diagnostic quality, improved over 5 years of experience, and with almost nominally nine-thousand MR scans. Although there are guidelines and recommendations for the development and implementation of a MR-planning program [8,9,13], and image acquisition protocols are available for specific sites [4,[14][15][16][17][18][19][20][21][22], very few reports have focused on describing clinical implementation experience with comprehensively detailing MR-planning programs [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our report is unique in addressing protocols for planning MR of sites that are not commonly detailed in the literature, such as breast or brachial plexus, and covering almost all tumour locations in the body. Even though planning MR is not routinely used for adjuvant breast radiotherapy, there has been growing interest in MR for partial breast irradiation, breast SBRT, and brachial plexus recurrences [16,18,19,[24][25][26]. For instance, planning MR has been performed in our institution as part of the ongoing phase I/II trial of SBRT for breast cancer patients who are inoperable or refuse breast surgery (ClinicalTrials.gov, NCT03585621).…”
Section: Discussionmentioning
confidence: 99%